2023
DOI: 10.3389/fcimb.2023.1096008
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine and its impact on the gut microbiota in colorectal cancer

Abstract: It is well-established that there are trillions of gut microbiota (GM) in the human gut. GM and its metabolites can reportedly cause cancer by causing abnormal immune responses. With the development of sequencing technology and the application of germ-free models in recent years, significant inroads have been achieved in research on GM and microbiota-related metabolites. Accordingly, the role and mechanism of GM in colorectal cancer (CRC) development have been gradually revealed. Traditional Chinese medicine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…In secondary bile acids, DCA and LCA have been shown to have cytotoxic and carcinogenic properties, the increased DCA and LCA in the colon lead to DNA oxidative damage and increased mitotic activity, leading to intestinal cell carcinogenesis, reducing the content of both exerting anti-tumor effects ( Shang et al, 2022 ). The abnormal increase of DCA and LCA also destroyed the intestinal mucosal barrier and induced intestinal inflammatory response to provide a microenvironment for cancer development and promotes the development of intestinal tumors ( Bu et al, 2023 ). Elevated levels of DCA and LCA in the colon activate cellular mechanisms, including the Wnt/β-catenin and NF-κB signaling pathways, leading to DNA oxidative damage and increased mitotic activity ( Jia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In secondary bile acids, DCA and LCA have been shown to have cytotoxic and carcinogenic properties, the increased DCA and LCA in the colon lead to DNA oxidative damage and increased mitotic activity, leading to intestinal cell carcinogenesis, reducing the content of both exerting anti-tumor effects ( Shang et al, 2022 ). The abnormal increase of DCA and LCA also destroyed the intestinal mucosal barrier and induced intestinal inflammatory response to provide a microenvironment for cancer development and promotes the development of intestinal tumors ( Bu et al, 2023 ). Elevated levels of DCA and LCA in the colon activate cellular mechanisms, including the Wnt/β-catenin and NF-κB signaling pathways, leading to DNA oxidative damage and increased mitotic activity ( Jia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional herbal medicine has gained widespread acceptance as an essential alternative and supplementary medicine that benefits cancer patients . Many studies have found that traditional medicinal plants, when taken as adjuvant treatment with radiotherapy, immunotherapy or chemotherapy, can increase quality of life, lengthen survival time, lessen side effects, and boost therapeutic effects. Owing to its efficiency and lack of negative side effects, the vital medicinal plant Curcuma aromatica Salisb (Cur) has been extensively utilized in traditional medicine. Several studies have showed the beneficial anticancer benefits of Cur. According to studies, Cur significantly reduces the risk of developing esophageal cancer via halting the reduction of manganese superoxide dismutase in the esophageal epithelium .…”
Section: Introductionmentioning
confidence: 99%
“… 11 Many studies have found that traditional medicinal plants, when taken as adjuvant treatment with radiotherapy, immunotherapy or chemotherapy, can increase quality of life, lengthen survival time, lessen side effects, and boost therapeutic effects. 12 14 Owing to its efficiency and lack of negative side effects, the vital medicinal plant Curcuma aromatica Salisb (Cur) has been extensively utilized in traditional medicine. 15 17 Several studies have showed the beneficial anticancer benefits of Cur.…”
Section: Introductionmentioning
confidence: 99%
“…In secondary bile acids, DCA and LCA have been shown to have cytotoxic and carcinogenic properties, the increased DCA and LCA in the colon lead to DNA oxidative damage and increased mitotic activity, leading to intestinal cell carcinogenesis, reducing the content of both exerting anti-tumor effects (Shang et al, 2022). The abnormal increase of DCA and LCA also destroyed the intestinal mucosal barrier and induced intestinal inflammatory response to provide a microenvironment for cancer development and promotes the development of intestinal tumors (Bu et al, 2023). Elevated levels of DCA and LCA in the colon activate cellular mechanisms, including the Wnt/β-catenin and NF-κB signaling pathways, leading to DNA oxidative damage and increased mitotic activity (Jia et al, 2018).…”
Section: Discussionmentioning
confidence: 99%